Synthesis of Silver Nanoparticles using Cellulose and Starch Extracted from Brewer Spent Grain: Assessment of their Antimicrobial and Preservatives Activities - Clement Olusola Ogidi; Ogo Philip Emmanuel; Olanrewaju Oludotun Daramola; Oyedolapo Bamigboye; Olu Malomo (Turkish Journal of Agriculture: Food Science and Technology, 2023)
Non-porous materials like cellulose and starch can be extracted from agro- industrial wastes and incorporated with nanoparticles for effective biotechnological purposes. In this study, silver nanoparticles (AgNps), silver-cellulose nanoparticles (AgNps-C) and silver-starch nanoparticles (AgNps-S) were characterized by UV-visible spectroscopy. Fourier transform infrared spectroscopy (FTIR) was used to identify viable biomolecules involved in capping and active stabilization of AgNps. Average sizes and morphologies of AgNps, AgNps-C and AgNps-S were further analyzed by scanning electron microscopy (SEM) and the percentage composition of each element was investigated by energy-dispersive X-ray spectroscopy (EDS). Antimicrobial activity of the synthesized AgNPs-C and AgNPs-S was tested against multiple antibiotic resistance microorganisms isolated from fish and meat. Zones of inhibition displayed by AgNPs-C and AgNPs-S ranged from 8.00 to 13.30 mm and 5.00 to 10.30 mm, respectively. The Minimum inhibitory concentration (MIC) for AgNPs-C and AgNPS-S ranged from 125 µg/mL to 500 µg/mL and 500 µg/mL to 1000 µg/mL, respectively. AgNPS-S and AgNPs-C inhibited the growth of microorganisms associated with spoilage of fish and meat. The bio-applications of AgNP –C and AgNP-S can be exploited in food industries as preservative agent or incorporated to packaging materials to elongate the shelf life of food products and reduce the side effects attributed to chemical preservative agents.